2013
DOI: 10.5713/ajas.2012.12439
|View full text |Cite
|
Sign up to set email alerts
|

National Genetic Evaluation (System) of Hanwoo (Korean Native Cattle)

Abstract: Hanwoo (Also known as Korean native cattle; Bos taurus coreanae) have been used for transportation and farming for a long time in South Korea. It has been about 30 yrs since Hanwoo improvement began in earnest as beef cattle for meat yield. The purpose of this study was to determine the trend of improvement as well as to estimate genetic parameters of the traits being used for seedstock selection based on the data collected from the past. Hanwoo proven bulls in South Korea are currently selected through perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
76
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(93 citation statements)
references
References 5 publications
13
76
4
Order By: Relevance
“…However, caution is needed to interpret genomic heritability since there may be bias in the likelihood estimate of the variance components caused by linkage equilibrium between some markers and QTLs (de los Campos et al, 2015). In this study, the estimated heritabilities did not differ much with the results of other studies regarding Hanwoo where the estimated heritability of CWT, BFT and EMA were 0.30-0.33, 0.27-0.41 and 0.35-0.50, respectively (Yoon et al, 2002;Park et al, 2013;Lee et al, 2014).…”
Section: Discussioncontrasting
confidence: 44%
“…However, caution is needed to interpret genomic heritability since there may be bias in the likelihood estimate of the variance components caused by linkage equilibrium between some markers and QTLs (de los Campos et al, 2015). In this study, the estimated heritabilities did not differ much with the results of other studies regarding Hanwoo where the estimated heritability of CWT, BFT and EMA were 0.30-0.33, 0.27-0.41 and 0.35-0.50, respectively (Yoon et al, 2002;Park et al, 2013;Lee et al, 2014).…”
Section: Discussioncontrasting
confidence: 44%
“…The same animal subset conversely showed relatively higher averages and lower variations for all carcass traits than those of PH+GEN, especially in their BF and MS traits. It is found that phenotypic measures in the present study were either in general agreement with a few earlier reports on Hanwoo cattle [17,18] or differed slightly being higher than others [19,20]. We also observed some noticeable differences in sample sizes among studies and that might explain some of the estimation variations with our study and other reports.…”
Section: Descriptive Statistics On Phenotypessupporting
confidence: 91%
“…The carcass traits used in the analyses were back-fat thickness (BFT), carcass weight (CWT), eye-muscle area (EMA), and marbling score (MAR). Park et al [11] reported heritabilities of 0.50, 0.30, 0.42 and 0.63 for BFT, CWT, EMA and MAR, respectively. Approval from the ethics committee was not required for these data since they were obtained from an existing industry database.…”
Section: Methodsmentioning
confidence: 99%